Hubungan Antara Pelatihan Kegawatdaruratan Dengan Kepuasan Kerja Perawat Di Instalasi Gawat Darurat - Brian Septa Setiyo Putro (Media Husada Journal Of Nursing Science, 2026)
Job satisfaction among Emergency Department (ED) nurses is a crucial factor as the ED constitutes the frontline service of the hospital. Emergency training is vital for enhancing competence and, subsequently, the nurses' job satisfaction. This study aims to determine the relationship between emergency training and job satisfaction among nurses in the ED of Dr. Saiful Anwar Regional General Hospital, East Java Province.This research employed a correlational study design (cross-sectional). The independent variable was emergency training, and the dependent variable was nurses' job satisfaction. Data were collected using a questionnaire administered to 44 nurses recruited via the Quota Sampling technique.The analysis results, using the Fisher's Exact Test, showed a significance value (p-value) of 0.024. Since the p<0.05, it is concluded that there is a significant relationship between emergency training and job satisfaction among nurses in the ED of Dr. Saiful Anwar Regional General Hospital, East Java Province. The training attended by the nurses was proven capable of increasing work motivation, which functions to influence, mobilize, and maintain work behavior toward achieving service goals. It is expected that these findings can provide input for the hospital management to maintain and enhance emergency training programs regularly. Keywords: Emergency_training; job_satisfaction; Emergency_Department.